The use of high-entropy alloys in additive manufacturing. (1st April 2015) - Brif, Yevgeni; Thomas, Meurig; Todd, Iain
Abstract : An equiatomic FeCoCrNi high-entropy alloy is used as an input material for selective laser melting. The material is characterized using X-ray diffraction, scanning electron microscopy, thermal analysis and mechanical testing to investigate the feasibility of using high-entropy alloys in additive manufacturing and the resulting tensile properties. Results show that not only does the alloy preserve its single-phase solid-solution state, but it also exhibits high strength and ductility that are comparable to engineering materials like stainless steels.